Ration fiber analysis - Morrill, J.L. (Kansas Agricultural Experiment Station, 2012)
For many years, fiber in dairy rations was measured and expressed as crude fiber. More recently acid detergent fiber (ADF) and neutral detergent fiber (NDF) have been used. The crude fiber (CF) determination uses acid and alkali treatment and is an attempt to simulate reactions within the digestive tract, whereas the newer techniques use detergents and attempt to divide the plant cells into their component parts. Thus, NDF is resistant to breakdown by a certain detergent in neutral solution and represents the structural part of the cell, the cell wall. Acid detergent fiber is resistant to breakdown by a certain detergent in acid solution and contains cellulose and lignin, the most undigestible carbohydrate fractions.
Keywords: Dairy; Ration; Fiber analysis; Crude fiber; Acid detergent fiber (ADF); Neutral detergent fiber